2009
DOI: 10.1111/j.1469-0691.2008.02229.x
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia rickettsii, Rickettsia felis and Rickettsia sp. TwKM03 infecting Rhipicephalus sanguineus and Ctenocephalides felis collected from dogs in a Brazilian spotted fever focus in the State of Rio De Janeiro/Brazil

Abstract: Rickettsia rickettsii, Rickettsia felis and Rickettsia sp. TwKM03 infecting Rhipicephalus sanguineus and Ctenocephalides felis collected from dogs in a Brazilian spotted fever focus in the State of Rio De Janeiro ⁄ Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 5 publications
0
20
1
11
Order By: Relevance
“…The proportion of positive pools (for the three genes) of cat fleas (54/132; 41%) is consistent with similar studies in different countries from all continents, confirming the worldwide distribution of this emergent pathogen. [2][3][4] However, the MIR reported here for C. felis (5.3%) is lower than MIRs reported in other countries, like Brazil (14.3%), 34 Taiwan (8.2%), 35 and the United States (13.3%). 33 We must emphasize that these rates correspond to MIRs, because they were calculated with the assumption that only one flea from each positive pool was positive for the Rickettsia gene analyzed; therefore, positive pools were not further corroborated to obtain the results for individual fleas, because we had limited resources.…”
Section: Discussioncontrasting
confidence: 47%
“…The proportion of positive pools (for the three genes) of cat fleas (54/132; 41%) is consistent with similar studies in different countries from all continents, confirming the worldwide distribution of this emergent pathogen. [2][3][4] However, the MIR reported here for C. felis (5.3%) is lower than MIRs reported in other countries, like Brazil (14.3%), 34 Taiwan (8.2%), 35 and the United States (13.3%). 33 We must emphasize that these rates correspond to MIRs, because they were calculated with the assumption that only one flea from each positive pool was positive for the Rickettsia gene analyzed; therefore, positive pools were not further corroborated to obtain the results for individual fleas, because we had limited resources.…”
Section: Discussioncontrasting
confidence: 47%
“…Although most reports on R. felis were associated to the flea Ctenocephalides felis felis collected in cats and/or dogs (LABRUNA et al, 2007b;NAVA et al, 2008;OLIVEIRA et al, 2008;GEHRKE et al, 2009), future studies should be conducted to fully establish flea rickettsial burden.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because A. aureolatum rarely attacks humans, the incidence of RMSF is also low in these specific areas of endemicity in southeastern Brazil (163). Finally, a number of recent studies from Brazil reported R. rickettsii infecting Rhipicephalus sanguineus ticks collected from dogs in areas where RMSF is endemic, where dogs are frequently infested by A. aureolatum or A. cajennense ticks (28,162,(164)(165)(166), and reports have also come from an area where RMSF is not endemic (167). As it has been shown that R. rickettsii is maintained by transstadial and transovarial transmission in Brazilian Rhipicephalus sanguineus ticks (26,28) and that the domestic dog is an efficient amplifier host of R. rickettsii in Rhipicephalus sanguineus ticks (26), studies are needed to elucidate the participation of this tick species in the epidemiology of RMSF in South America.…”
Section: South Americamentioning
confidence: 99%